2015
DOI: 10.1111/all.12581
|View full text |Cite
|
Sign up to set email alerts
|

Sustained effect of grass pollen subcutaneous immunotherapy on suppression of allergen‐specific basophil response; a real‐life, nonrandomized controlled study

Abstract: Grass pollen immunotherapy induces sustained suppression of the allergen-specific basophil response that persists after completion of treatment and could account for long-term clinical tolerance. It also seems to be associated with persistent blocking activity of IgG antibodies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 23 publications
2
32
0
1
Order By: Relevance
“…These contrasting findings may be partly explained by the route of immunotherapy, with SLIT being possibly less effective in inhibiting basophils than SCIT. Several studies show that basophil activation decreases after AIT, not only at the level of CD63 or CD203c, but also as measured by decreased DAO and increased CD107a . One study using DAO has shown persistent basophil suppression in four subjects 12–24 months after stopping AIT .…”
Section: Resultsmentioning
confidence: 99%
“…These contrasting findings may be partly explained by the route of immunotherapy, with SLIT being possibly less effective in inhibiting basophils than SCIT. Several studies show that basophil activation decreases after AIT, not only at the level of CD63 or CD203c, but also as measured by decreased DAO and increased CD107a . One study using DAO has shown persistent basophil suppression in four subjects 12–24 months after stopping AIT .…”
Section: Resultsmentioning
confidence: 99%
“…In subjects suffering from seasonal pollen‐allergic rhinitis, SCIT induces a strong decrease in basophil sensitivity during the updosing phase . These early changes in basophil sensitivity were shown to predict clinical outcome in the following pollen season and are maintained throughout maintenance therapy and even after treatment cessation . A protocol of preseasonal injections also reduced the basophil response .…”
Section: Biomarkers For Diagnosis and Monitoring In Ait Trialsmentioning
confidence: 99%
“…(68) Suppression of basophil activation has been associated with immunotherapy to both environmental(9, 10) and food allergens. (1, 1114) Historically, identification of rare cells such as basophils has been difficult with flow cytometry due to their relative scarcity (15, 16) However, wide-spread adoption of this flow cytometry-based test has been limited by the intensive nature of analysis and interpretation required for flow cytometry data by expert operators.…”
Section: Introductionmentioning
confidence: 99%
“…Measurement of antigen-induced basophil activation ex vivo has been shown to be a promising diagnostic test in many allergic disorders (6)(7)(8). Suppression of basophil activation has been associated with immunotherapy to both environmental (9,10) and food allergens (1,(11)(12)(13)(14). Historically, identification of rare cells such as basophils has been difficult with flow cytometry due to their relative scarcity (15,16).…”
Section: Introductionmentioning
confidence: 99%